Murray Bookchin; Dari Bolshevik ke Marxis Otonomis - Putra, Moch. Rizky Pratama (The Sociology of Islam, 2022)
This study discusses a brief biography of Murray Bookchin's revolutionary journey by tracing his activism and intellectual movements. This study uses a literary or library research approach, namely a comparative study to explore and trace the life journey of Bookchin. Boochin's long history of involvement in the revolutionary movement was inherited directly by his grandmother Zeitel Carlat who was a combatant in the war against the dictatorship of the Tsarist Empire. Zeitel who grew up with a liberal and secular education from the Haskalah tradition then passed his ideas on to his children, one of whom was Bookchin's mother, Rose. Rose is very different from her mother Zeitel. The difference was clearly illustrated when Rose chose to join the Russian Anarchist Workers' Union rather than join the American Communist Party. Over time Rose later married Nathan, a fellow Jewish immigrant. However, because Zeitel's hatred for Nathan was so strong, Rose and Nathan's relationship had to end. It was at this moment that Bookchin was first educated directly by his grandmother. From a young age, Bookchin was introduced to Russian revolutionary traditions, such as Stenka Razin, the leader of the Cossack rebellion and the large-scale peasantry in southeastern Russia. This search process is an attempt to elaborate and trace the background of Murray Bookchin's life so that he can find his own concept of thinking, namely dialectical naturalism and the concept of social ecology which has an important contribution to the dimensions of social science, especially sociology.